The potential of virtual representations to help students in learning mathematics - Sari, Yurizka Melia; Arlinwibowo, Janu; Fatima, Gupita Nadindra; Purwoko, Dwi; Suprapto, Suprapto (Institute of Advanced Engineering and Science, 2024)
The study aims to conclude the benefits of virtual representation in helping students learn mathematics. To answer this goal, this research utilizes the meta-analysis method of two-group difference design. The data collection process used inclusion criteria. The data collection process was carried out with the PRISMA. The results of the effect analysis of the p-value < 5% (95% confidence interval) and the total effect of 1.1761 so that virtual representation has a significant influence. The analysis showed that i) implementation in each continent showed identical positive effects, ii) the number of students subjected to the treatment did not make a difference, iii) themes in mathematics were equally well affected with the help of virtual representation, iv) the effect of virtual representation in junior high school, high school, and university was identical, v) the development of competencies in attitude, knowledge, and skills was equally good, vi) among the many applications, GeoGebra was the application that had the greatest impact in helping students understand mathematics subject matter, and vii) the use of smartphones had a greater effect than other devices such as computers and calculators. To produce the maximum effect in understanding students, it is recommended to use mobile devices and GeoGebra software.